2004
DOI: 10.1002/app.20946
|View full text |Cite
|
Sign up to set email alerts
|

Development of a fixed‐bed column with cellulose/chitin beads to remove heavy‐metal ions

Abstract: Environmental friendly cellulose/chitin beads, having relatively high mechanical properties, were successfully prepared from a blend of cellulose and chitin in 6 wt % NaOH/5 wt % thiourea aqueous solution by coagulating with 5% H 2 SO 4 aqueous solution. The ability of the beads to adsorb Pb 2ϩ in an aqueous solution was measured with a fixed-bed column. The effects of important parameters, to design an adsorption column of the cellulose/chitin beads for fixed-bed columns, were investigated. The breakthrough c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 32 publications
0
29
0
1
Order By: Relevance
“…Biosorption is a complementary, inexpensive, and easy method in such applications [35,36]. To this end, chitin has been known to chelate heavy metal ions for wastewater treatment purposes [28,30,[36][37][38][39]. Barriada et al, have reported on the removal of cadmium and lead from contaminated effluents by chitin chelation [40].…”
Section: Chitin and Chitosanmentioning
confidence: 99%
See 1 more Smart Citation
“…Biosorption is a complementary, inexpensive, and easy method in such applications [35,36]. To this end, chitin has been known to chelate heavy metal ions for wastewater treatment purposes [28,30,[36][37][38][39]. Barriada et al, have reported on the removal of cadmium and lead from contaminated effluents by chitin chelation [40].…”
Section: Chitin and Chitosanmentioning
confidence: 99%
“…Similarly, vanadate and chromium cations, in addition to cadmium, copper, lead, and zinc have been adsorbed by chitin [35,41]. Moreover, it was also reported that lead as well as iron cations are adsorbed on chitin [37]. It should be mentioned here that cadmium, chromium, mercury, zinc, copper, lead, iron, silver, molybdenum, and nickel are major pollutants in industrial wastewater and are of particular interest for removal given the serious problems these metals can cause in the environment [28].…”
Section: Chitin and Chitosanmentioning
confidence: 99%
“…[7] reported column diameters of 30 mm, 2.0 -2.5 cm was reported by [4] [8] 5 cm was reported [9] and 20 cm by [10] have been employed. To minimize possible wall and axial dispersion effects in fixed columns, it is recommended that the bed length-to-particle diameter ratio be greater than 20 [4]. It could be deduced that the axial dispersion effects could be avoided if the adsorbent particle size is larger by using a deeper column or adsorbent with smaller particle size diameter.…”
Section: Methodsmentioning
confidence: 99%
“…From this, the concept of breakthrough can be defined as the amount of influent solution passing through the bed before a maximum effluent concentration is reached [3] [4]. Breakthrough and exhaustion are defined as the phenomena when the ratios of effluent-to-influent concentrations are 5% and 95% respectively [4]. Values of column breakthrough and exhaustion are often used to evaluate adsorption parameters in column adsorption systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation